1999
DOI: 10.2343/geochemj.33.305
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polycyclic aromatic hydrocarbons in the K/T boundary sediments at Kawaruppu, Hokkaido, Japan.

Abstract: , JapanTwenty six polycyclic aromatic hydrocarbons (PAHs) from naphthalene to coronene were found in the K/T boundary sediments at Kawaruppu, Hokkaido, Japan and their concentrations were estimated except for naphthalene. Another 28 PAHs were found qualitatively. The total concentration of those 25 PAHs (except naphthalene) in each sediment was in the range of 2.3 to 11.4 nmol g-1 and showed no specific feature for the boundary claystone or for sediments above and below it. Individual PAHs were present at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…This period is too short to make a significant difference in the ratio between the top and bottom sediments of 65 million years old. A similar type result was reported for the ratios of β-to α-alkylated PAHs, such as 2-to 1-methylnaphthalene, 2-to 1-methylphenanthrene and 3-to 1-methylphenanthrene, which were found to be roughly constant in the Kawaruppu sediments (Mita and Shimoyama, 1999b). Therefore, it is likely that the 65 million year diagenesis has taken place evenly over the sediments above, within, and below the boundary claystone for the DBTs as well as the PAHs.…”
Section: Fig 4 Mass Fragmentograms Of Polynuclear Aromatic Thiophensupporting
confidence: 63%
See 2 more Smart Citations
“…This period is too short to make a significant difference in the ratio between the top and bottom sediments of 65 million years old. A similar type result was reported for the ratios of β-to α-alkylated PAHs, such as 2-to 1-methylnaphthalene, 2-to 1-methylphenanthrene and 3-to 1-methylphenanthrene, which were found to be roughly constant in the Kawaruppu sediments (Mita and Shimoyama, 1999b). Therefore, it is likely that the 65 million year diagenesis has taken place evenly over the sediments above, within, and below the boundary claystone for the DBTs as well as the PAHs.…”
Section: Fig 4 Mass Fragmentograms Of Polynuclear Aromatic Thiophensupporting
confidence: 63%
“…The depth profiles of these polynuclear aromatic thiophenes are quite different from that of the C 25 HBI thiophene and do not show an event directly related to the massive extinction. Furthermore, the distributions of the polynuclear aromatic thiophenes are not consistent with those of total and individual PAHs (Mita and Shimoyama, 1999b), indicating that the formation pathways of those thiophenes were likely different from those of the PAHs in the sediments. A portion of the PAHs within the boundary claystone is considered to be of combustion origin (Mita and Shimoyama, 1999b).…”
Section: Fig 4 Mass Fragmentograms Of Polynuclear Aromatic Thiophenmentioning
confidence: 82%
See 1 more Smart Citation
“…In the present study we analyzed free and bound maleimides in the K/T boundary sediments at Kawaruppu in order to obtain another example illustrating the utility of maleimides as biomarkers, as well as to examine maleimide distribution in a sedimentary sequence differing in maturity from that of the Shinjo sediments. Previous studies indicated that the 65 million year diagenesis has taken place evenly over the sediments throughout the sequence (Mita and Shimoyama, 1999a;Katsumata and Shimoyama, 2001). Organic geochemical studies of amino acids (Mita et al, 1996) and dicarboxylic acids (Mita et al, 1998) in the sediments were discussed as to the possibility of the presence of extraterrestrial organic compounds as well as terrestrial ones.…”
Section: Introductionmentioning
confidence: 99%
“…Organic geochemical studies of amino acids (Mita et al, 1996) and dicarboxylic acids (Mita et al, 1998) in the sediments were discussed as to the possibility of the presence of extraterrestrial organic compounds as well as terrestrial ones. Characteristic distributions of aliphatic hydrocarbons (Mita and Shimoyama, 1999b) and polycyclic aromatic hydrocarbons (PAHs) (Mita and Shimoyama, 1999a) in the sediments were reported and related to the massive extinction and wildfires, respectively.…”
Section: Introductionmentioning
confidence: 99%